Digital Payment Gopay in Students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara - Gunawan, Ade; Azzahra, Tiara Bulan (Journal of International Conference Proceedings, 2023)
The purpose of this study was to determine and analyze the effect of trust, convenience, security and promotion on student decisions in using go pay either partially or simultaneously. The approach used in this study is an associative approach. The population in this study are all students who use gopay. The sample in this study used a saturated sample with 100 samples. Data collection techniques in this study used interview techniques, documentation studies, observations, and questionnaires. Data analysis techniques in this study used Multiple Liner Regression Analysis Test, Hypothesis Test (t test and F test), and the Coefficient of Determination. Data processing in this study used the SPSS (Statistics Package for the Social Sciences) software version 24.00. The results of this study prove that trust, convenience, security and promotion influence student decisions in using go pay either partially or simultaneously.